Voltage-gated potassium channels autoantibodies in a child with rasmussen encephalitis. - Spitz, M; Dubois-Teklali, F; Vercueil, L; Sabourdy, C; Nugues, F; Vincent, A; Oliver, V; Bulteau, C (2014)
Rasmussen encephalitis (RE) is a severe epileptic and inflammatory encephalopathy of unknown etiology, responsible for focal neurological signs and cognitive decline. The current leading hypothesis suggests a sequence of immune reactions induced by an indeterminate factor. This sequence is thought to be responsible for the production of autoantibody-mediated central nervous system degeneration. However, these autoantibodies are not specific to the disease and not all patients present with them. We report the case of a 4-year-old girl suffering from RE displaying some atypical features such as fast evolution and seizures of left parietal onset refractory to several antiepileptics, intravenous immunoglobulins, and corticosteroids. Serum autoantibodies directed against voltage-gated potassium channels (VGKC) were evidenced at 739 pM, a finding never previously reported in children. This screening was performed because of an increased signal in the temporolimbic areas on brain magnetic resonance imaging, which was similar to what is observed during limbic encephalitis. The patient experienced epilepsia partialis continua with progressive right hemiplegia and aphasia. She underwent left hemispherotomy at the age of 5.5 years after which she became seizure free with great cognitive improvement. First described in adults, VGKC autoantibodies have been recently described in children with various neurological manifestations. The implication of VGKC autoantibodies in RE is a new observation and opens up new physiopathological and therapeutic avenues of investigation.